Factors influencing the adoption of big data analytics in the South African financial services industry - Mthethwa, Siyabonga (University of the Witwatersrand, Johannesburg, 2023)
The rapid expansion of big data analytics (BDA) presents significant prospects for organizations across industries, including the financial services sector. This research investigated the factors that influence the adoption of BDA within the South African financial services industry, examining their impact on investment decision-making and the evaluation of post-implementation value. A comprehensive research framework is employed to accomplish these objectives, combining the Technological, Organizational, and Environmental (TOE) framework with the BDA Adoption model. The TOE framework provides a contextual understanding of technological, organisational, and environmental factors, while the BDA Adoption model specifically focuses on moderating factors such as paradigm shift and organisation’s complexity tolerance for big data analytics adoption. Data is gathered from diverse stakeholders in the South African financial services industry through a qualitative approach encompassing semi-structured interviews. Thematic analysis method was used to analyse the data gathered from the interviews. The findings of this study indicate that organizations characterized by a higher tolerance for complexity are more prone to achieving a seamless transition from the intention of adopting BDA to its successful deployment. This study also found that a combination of factors such as top management support, relative advantage, trialability, human resource, regulatory environment and vendor support did influence investment decision-making collectively. Also, the push from the regulators and the need by financial organisations to improve customer experience led to an acceleration of BDA adoption, which ultimately led to investment decisions being made to meet these objectives. The outcomes of this research will contribute to the growing body of knowledge on BDA adoption by offering unique insights into the factors specific to the South African financial services industry. Furthermore, the findings will assist organizations operating within this sector in making well-informed decisions iii regarding BDA adoption, optimizing their investments, and maximizing the value obtained from the implementation of BDA technologies
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Adoption; Big data analytics; complexity tolerance; Deployment gap; Complexity tolerance; Financial service industry; UCTD; SDG-8: Decent work and economic growth